2017
DOI: 10.3389/fneur.2017.00353
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Movements As Accurate Reporters of Respiratory Effort during Sleep: Validation against Diaphragmatic Electromyography

Abstract: ContextMandibular movements (MM) are considered as reliable reporters of respiratory effort (RE) during sleep and sleep disordered breathing (SDB), but MM accuracy has never been validated against the gold standard diaphragmatic electromyography (EMG-d).ObjectivesTo assess the degree of agreement between MM and EMG-d signals during different sleep stages and abnormal respiratory events.MethodsTwenty-five consecutive adult patients with SDB were studied by polysomnography (PSG) that also included multipair esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…This is known to typically indicate an underlying exaggerated respiratory effort. 4,5 The spectral analysis comparison between masseteric and limb EMG during the episode of bruxism shows that contractions of jaw muscles are not nonspecific motor phenomena in response to arousals. 9 By closing the mouth and stretching the upper airways muscles, mandibular motion contributes to airflow restoration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is known to typically indicate an underlying exaggerated respiratory effort. 4,5 The spectral analysis comparison between masseteric and limb EMG during the episode of bruxism shows that contractions of jaw muscles are not nonspecific motor phenomena in response to arousals. 9 By closing the mouth and stretching the upper airways muscles, mandibular motion contributes to airflow restoration.…”
Section: Discussionmentioning
confidence: 99%
“…During respiratory effort, this amplitude increases to > 0.3 mm, a finding which was validated by measurement of pulse transit time 4 or electromyographic activity of the diaphragm. 5 Cortical arousals are marked by large abrupt MMs.…”
Section: Case Reportmentioning
confidence: 99%
“…Mandibular movement analysis has been validated as an accurate measurement modality of respiratory effort during sleep, providing information on the obstructive or central nature of respiratory events. 24 Compared with other simplified diagnostic techniques, MM also provides reliable estimation of TST and unbiased identification of microarousals. 26,27 Correct TST calculation prevents RDI underestimation (relative to the total recording time), and microarousal identification ensures recognition of respiratory effort-related arousals.…”
Section: Sunrise System and High-performance Sleep Apnea Diagnosismentioning
confidence: 99%
“… 24 Several studies have shown that jaw movement analysis is a reliable method for distinguishing sleep-wake status and thus can be used as an alternative to actigraphy. 25 27 The device can recognize the nature of SDB: central or obstructive. Supplemental Appendix 2 presents the Somnolter® device appearance and a screenshot of recorded signals.…”
Section: Methodsmentioning
confidence: 99%
“…We relied on the Jawac signal to estimate sleep-wake status and arousals. 25,26 Another limitation was that HSAT was performed only for one night, and night-to-night variability can also cause some misclassification.…”
Section: Strengths and Limitationsmentioning
confidence: 99%